Meta-analysis of Chinese business cycle correlation - Jarko Fidrmuc; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
We summarize previous research on China's business cycle correlation with other countries with the help of meta-analysis techniques. We survey 71 related papers along with all the characteristics of the estimations as well as those of the authors. We confirm that especially Pacific Rim countries have relatively high business cycle correlation with China. However, it appears that many characteristics of the studies and authors do influence the reported degree of business cycle synchronization. For instance, Chinese-language papers report higher correlation coefficients. Despite of this, we do not detect a robust publication bias in the papers.
URN:NBN:fi:bof-201503111109
Keywords: E32; F44; 330